An application of DEA to the third sector: the case of children and youth households - Vaz, Clara B. (2018)
The Portuguese state has transferred some areas of its social program for third sector entities, including private social welfare institutions. This transfer of powers is supported by providing economic subsidies, being public entities responsible to monitor the efficient management by those institutions. This research aims to present a contribution to monitor the efficient management of resources by the institutions that look after children and young people. The DEA method is used to assess the technical efficiency of eight institutions from Bragança district, during the years 2010 to 2013. This model evaluates each institution in reduction of resource levels used to provide social services to the level of users observed in each unit. This approach should be used to complement the assessment of quality in providing social services, which is currently performed by the regulator, in order to allow monitoring the overall performance of such institutions.